Industrialization of a perfusion bioreactor: Prime example of a non‐straightforward process. (8th October 2017) - Talò, G.; Turrisi, C.; Arrigoni, C.; Recordati, C.; Gerges, I.; Tamplenizza, M.; Cappelluti, A.; Riboldi, S.A.; Moretti, M.
Abstract: Bioreactors are essential enabling technologies for the translation of advanced therapies medicinal products from the research field towards a successful clinical application. In order to speed up the translation and the spread of novel tissue engineering products into the clinical routine, tissue engineering bioreactors should evolve from laboratory prototypes towards industrialized products. In this work, we thus challenged the industrialization process of a novel technological platform, based on an established research prototype of perfusion bioreactor, following a GMP‐driven approach. We describe how the combination of scientific background, intellectual property, start‐up factory environment, wise industrial advice in the biomedical field, design, and regulatory consultancy allowed us to turn a previously validated prototype technology into an industrial product suitable for serial production with improved replicability and user‐friendliness. The solutions implemented enhanced aesthetics, ergonomics, handling, and safety of the bioreactor, and they allowed compliance with the fundamental requirements in terms of traceability, reproducibility, efficiency, and safety of the manufacturing process of advanced therapies medicinal products. The result is an automated incubator‐compatible device, housing 12 disposable independent perfusion chambers for seeding and culture of any perfusable tissue. We validated the cell seeding process of the industrialized bioreactor by means of the Design of Experiment approach, whilst the effectiveness of perfusion culture was evaluated in the context of bone tissue engineering.